Arginina no desempenho produtivo e respostas fisiológicas de tilápia produzida em tanque-rede - Santos, Rudã Fernandes Brandão [UNESP] (2015)
This review explores the effects of arginine supplementation in health and productive aspects of fish. The use of arginine in diet showed influence on fish physiological response according to the dose applied. The aspects studied by the authors were grouped into ten main themes: effects of arginine in the digestive system and absorption of nutrients; digestibility and circulating arginine in plasma; analytes and enzymes related to diet; hematological indices; gene expression and hormone secretion; liver function; and oxidative immune response; body indexes; chemical composition and productive performance. Arginine has a significant effect on growth performance and on variables related to nutrients retention. Is evident its association with increased nitrogen excretion by fish, however, interaction between lysine and arginine needs to be further investigated since it is not clear the presence of antagonism between these amino acids. In health, is not elucidated variables response due to arginine supplementation. The challenges performances, either by management or by bacterial infection, have proved being an excellent tool to assess the effect of this amino acid immunostimulant. Due to its release by phagocytic cells and its bactericidal action, nitric oxide synthesis by arginine is extremely important. Thus, arginine displays high potential as dietary additive